2004
DOI: 10.1634/theoncologist.9-6-708
|View full text |Cite
|
Sign up to set email alerts
|

Cancer as Metaphor

Abstract: Shortly before his death in 1995, Kenneth B. Schwartz, a cancer patient at Massachusetts General Hospital (MGH), founded The Kenneth B. Schwartz Center at MGH. The Schwartz Center is a nonprofit organization dedicated to supporting and advancing compassionate health care delivery, which provides hope to the patient and support to caregivers and encourages the healing process. The center sponsors the Schwartz Center Rounds, a monthly multidisciplinary forum where caregivers reflect on important psychosocial iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 16 publications
0
84
0
3
Order By: Relevance
“…This is despite the fact that much of the scientific research highlighted in the printed press over the five year time frame of this study was still in development and often untested in humans. Terms such as 'attack' , 'destroying' , 'struggle' , and 'battle' , which were readily written by journalists in reference to RA, seemed to draw on metaphors of warfare [57][58][59]. Lakoff and Johnson [60] have suggested that conceptual systems are designed to function in a metaphorical sense.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is despite the fact that much of the scientific research highlighted in the printed press over the five year time frame of this study was still in development and often untested in humans. Terms such as 'attack' , 'destroying' , 'struggle' , and 'battle' , which were readily written by journalists in reference to RA, seemed to draw on metaphors of warfare [57][58][59]. Lakoff and Johnson [60] have suggested that conceptual systems are designed to function in a metaphorical sense.…”
Section: Discussionmentioning
confidence: 99%
“…That is, metaphors allow us to communicate concepts that are abstract or complex in simplified terms [60]. Metaphoric language has a long and durable history in medicine [57][58][59]61]. Metaphors of transgression and punishment have been commonly used in tuberculosis (TB) research and clinical practice [61], and military metaphors are a noticeable feature of discourses around the medical treatment of cancer [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Or participants might use the poem to reflect on the effects of metaphor in medicine, considering how the metaphors used to describe diseases and treatments shape the expectations of patients and practitioners, in ways that can be edifying, empowering, obfuscating, or even unintentionally harmful. [6][7][8][9] At a conference on alleviating burnout, physicians spoke candidly about personal and professional griefs they carry, griefs that they seldom have opportunities to speak about, let alone to ameliorate through the kinds of connections we forged while discussing the poem.…”
Section: Narrative Medicine Finding Purpose: Honing the Practice Of Mmentioning
confidence: 99%
“…4,[6][7][8] In other health-related conversations, physicians and patients may use metaphors and analogies to enhance their ability to communicate effectively. [9][10][11][12][13][14][15][16][17] However, it is not known how often physicians use metaphors and analogies to enhance communication with patients who are seriously ill. Nor is it known whether metaphors and analogies improve patients' perceptions of a physician's communication.…”
mentioning
confidence: 99%